Environmental Impact Assessment of the Tidal Link Failure and Sea Intrusion on Ramsar Site No. 1069 - Mahessar, A. A.; Laghari, A. N.; Qureshi, S.; Siming, I. A.; Qureshi, A. L.; Shaikh, F. A. (Engineering, Technology & Applied Science Research, 2019)
This paper presents the impact on the RAMSAR site No. 1069 that receives fresh water by the Kotri drainage system. At present, the complex faces threats by effluents from the Left Bank Outfall Drain (LBOD) system and from saline seawater intrusion during high tides. These threats have destroyed the ecosystem of the lakes Cholari, Mehro, Pateji and Sanhro belonging to the complex. The total present lake area, maintained at the Cholari weir crest level, is about 170km2. The lakes are expanding, available data shows that there is an increase up to 700% in the original lakes’ area, from 6058 to 41220 acres from 1954 to 1977. This is mainly caused by the operation of Kotri Barrage surface drainage system and has positive impact on lakes’ ecology because the drainage effluent is of marginal salinity. The rapid increase in the lakes’ area, of about 40% within 2 years after the functioning of the Tidal Link with saline effluents from LBOD and sea intruded water have changed the ecology of the area. This posed a significant impact on the ecosystem. Conversely, a similar rise in water level due to sea intrusion has nearly doubled the surface area and reposed a negative impact on the system. These lakes were giving shelter to a wide variety of local and migratory birds and had aquatic biodiversity. Hence, parts of Sanhro and Mehro dhands have been recognized by the RAMSAR Convention